Pengembangan Gim Edukasi Mengenai Narkoba Berbasis Desktop - Muhammad Ahimsa Dhia; Harya Bima Dirgantara (UNIVERSITAS KALBIS, 2022)
This study discusses the development of an educational desktop-based game that addresses narcotics, psychotropics, and addictive substances. This